2017
DOI: 10.1097/aap.0000000000000573
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Suprascapular Nerve Block Versus Interscalene Brachial Plexus Block for Shoulder Surgery in the Outpatient Setting

Abstract: For outpatients undergoing arthroscopic shoulder surgery under general anesthesia, the SSNB seems preferable to ISB. It provides excellent postoperative analgesia without exposing patients to impaired mobility and to risks of the more potent but also more invasive ISB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 25 publications
3
58
0
1
Order By: Relevance
“…Ten millilitres is a high volume and there is likely to have been local anaesthetic spread to the phrenic nerve with this volume. Nevertheless, it corresponds with the literature regarding suprascapular nerve blocks . Further studies using lower volume (e.g.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Ten millilitres is a high volume and there is likely to have been local anaesthetic spread to the phrenic nerve with this volume. Nevertheless, it corresponds with the literature regarding suprascapular nerve blocks . Further studies using lower volume (e.g.…”
Section: Discussionsupporting
confidence: 85%
“…The suprascapular and axillary nerves provide sensory innervation to most of the glenohumeral joint [14][15][16]. Therefore, a combined suprascapular and axillary nerve block is a valid alternative to interscalene brachial plexus block [4] with less impact on respiratory function [17][18][19][20][21][22] and hand-grip strength [23].…”
Section: Introductionmentioning
confidence: 99%
“…Beside axillary/suprascapular 2,3 and infraclavicular/suprascapular nerve blocks, 4 proposed strategies also include isolated suprascapular nerve blocks. 19,20 Although recent trials by Wiegel et al 19 and Auyong et al 20 have concluded that suprascapular blocks result in similar analgesia to ISB for arthroscopic shoulder surgery 19 and shoulder arthroplasty, 20 other studies seem to suggest that they provide suboptimal analgesia. 21,22 Because the shoulder also receives sensory innervation from the axillary, lateral pectoral, and subscapular nerves, 1 we decided to err on the side of caution and attempted to find an alternative to ISB that would anesthetize all these nerves.…”
Section: Discussionmentioning
confidence: 99%
“…It has been modified multiple times, is technically challenging and has shown conflicting results 8. The anterior approach (in the supraclavicular fossa) has been recently proposed as a reliable and easy technique9 with similar efficacy for shoulder surgery 10. However, the proximity to the brachial plexus in this region may result in a potential extension of local anesthetic to the phrenic nerve if conventional large volumes are used.…”
Section: Introductionmentioning
confidence: 99%